2016
DOI: 10.3791/52224
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Regulation by Continuous Feeding for Large-scale Expansion of Mammalian Cells in Spheroids

Abstract: In this demonstration, spheroids formed from the β-TC6 insulinoma cell line were cultured as a model of manufacturing a mammalian islet cell product to demonstrate how regulating nutrient levels can improve cell yields. In previous studies, bioreactors facilitated increased culture volumes over static cultures, but no increase in cell yields were observed. Limitations in key nutrients such as glucose, which were consumed between batch feedings, can lead to limitations in cell expansion. Large fluctuations in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The complexity, cost, and time-consuming nature of primary islets of Langerhans research and training motivated our team to create an accessible, rapidly renewable, and representative model system for isolated islets that could be used to train personnel and inform experiments that require valuable primary islets. Previous work by several groups has shown that insulinoma cell lines form islet-like aggregates or IPIs (13)(14)(15)(16)(17)(18)(19)(20)34). However, previous approaches to create IPIs required relatively complex methodology, often with relatively low yields and limited functional characterization.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity, cost, and time-consuming nature of primary islets of Langerhans research and training motivated our team to create an accessible, rapidly renewable, and representative model system for isolated islets that could be used to train personnel and inform experiments that require valuable primary islets. Previous work by several groups has shown that insulinoma cell lines form islet-like aggregates or IPIs (13)(14)(15)(16)(17)(18)(19)(20)34). However, previous approaches to create IPIs required relatively complex methodology, often with relatively low yields and limited functional characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, co-microencapsulation of BMSCs and mouse pancreatic β cells (beta-TC-6) was performed in the current study. Beta-TC-6 was selected due to its more sensitive response to glucose (21) through the activation of ERK 1/2 signal transduction pathway (22), and the ability for large-scale expansion in spheroids (23). Their insulin secretion and their potential for transplantation for treatment of type I diabetes were then investigated.…”
Section: Introductionmentioning
confidence: 99%